A phase II, single‐center, double‐blind, randomized placebo‐controlled trial to explore the efficacy and safety of intravenous melatonin in surgical patients with severe sepsis admitted to the intensive care unit. Issue 2 (2nd December 2022) - Mansilla‐Roselló, Alfonso; Hernández‐Magdalena, Jorge; Domínguez‐Bastante, Mireia; Olmedo‐Martín, Carmen; Comino‐Pardo, Ana; Escames, Germaine; Acuña‐Castroviejo, Darío
Abstract: To determine whether IV melatonin therapy improves redox status and inflammatory responses in surgical patients with severe sepsis, a unicenter, phase II double‐blind, randomized, placebo‐controlled trial was carried out. The study included patients with severe sepsis marked by infectious systemic inflammatory response syndrome (SIRS), associated with organ dysfunction, hypoperfusion or hypotension requiring surgical intervention. IV melatonin at a daily dose of 60 mg, which was dissolved in 500 ml of 5% dextrose serum, was continuously administered to the patients for over 30 min starting on the day of the diagnoses during a 5‐day period. A total of 14 patients received a placebo treatment and 15 melatonin doses. Redox status decreased in melatonin‐treated patients during the 5 days of treatment as compared to the placebo‐treated patients. Procalcitonin performed better in the melatonin group, whose neutrophil to lymphocyte ratio was also significantly reduced, resulting in an improved evolution of the disease. Moreover, hospital stays decreased by 19.60% from 26.64 days for the placebo group to 21.42 days for the melatonin group. The placebo group recorded five mortalities, as compared to three for the melatonin group. IV melatonin administration improved the course of the disease in surgical patients with severe sepsis, with no side effects. Additional studies with higher doses of melatonin and a long duration of therapy need to be carried out to assess its clinical use.